EFFECTS OF REWARD STRATEGIES ON EMPLOYEE PERFORMA NCE IN REMITTANCE COMPANIES IN MOGADISHU, SOMALIA. - ADAN NOOR, ABDIWELI; GICHINGA, DR. LUCY (IJRDO - Journal of Business Management, 2016)
The purpose of this study was to examine the effect of reward strategies on employee performance in remittance companies in Mogadishu, Somalia. The study adopted the descriptive research design. The population under the study was 186 employees of Dahabshiil, Amal Express, and Kaah Express three remittance companies in Mogadishu, Somalia. A sample of 127 employees selected using stratified random sampling. Data collected using selfadministered questionnaires. Data was analyzed using SPSS version 20. In general, the results revealed that extrinsic reward strategy, intrinsic reward strategy, and contingent reward strategy have significant and positive effects on employee performance of remittance companies in Mogadishu, Somalia. Conclusions the overall results indicated that there was a significant linear relationship between extrinsic reward strategy, intrinsic reward strategy, contingent reward strategy and employee performance of remittance companies in Mogadishu The study recommends that the remittance companies should continues to offer total rewards to its employees, so there needs both intrinsic and extrinsic can be met, which leads to motivation and performance levels.